A CASE STUDY ON RIGHT TO PRIVACY - Tiwari, Shilpa; Mishra, Khusbhu S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This case study examines the concept of the Right to Privacy, analyzing its evolution, legal status, challenges, and implications for individuals and societies. With a focus on India, it explores the role of the judiciary in recognizing privacy as a fundamental right, particularly through the landmark Puttaswamy Judgment. The study highlights the balance between privacy and national security, technological advancements, and the growing concerns regarding data protection. Through legal analysis and empirical data, the study aims to provide a comprehensive understanding of privacy issues and suggests measures to safeguard this right in the digital era.